Profile of Vocabulary Learning of Vocabulary Masters of STIMIK Amikom and ABA Sinema Yogyakarta - Marita Nurharjanti; Imam Ghozali (Journal of English Language and Pedagogy, 2018)
Vocabulary mastery is one of the goals of language learning. Vocabulary is very important because it is one of the most functional language elements needed to perform communication. This paper reports a case study on vocabulary learning by a group of adult students learning English in two different universities. The objective of this research is to describe the profile of the vocabulary learning of the ten best vocabulary masters in two private universities. The research involved 5 students from STMIK Amikom and 5 students from ABA Sinema; both are in Yogyakarta. Those participants were chosen based three criteria; their cognitive, affective and psychomotor factors. The findings show that the masters develope varying degree of their receptive as well as the productive skills; second, the masters learn from authentic material because it is more effective; third, in order to produce a better translation, the vocabulary masters review results of their internet-based translation due to their lack of grammatical use.